2010
DOI: 10.1061/(asce)ee.1943-7870.0000182
|View full text |Cite
|
Sign up to set email alerts
|

Biocover Performance of Landfill Methane Oxidation: Experimental Results

Abstract: An experimental passive methane oxidation biocover (PMOB) was constructed within the existing final cover of the St-Nicéphore landfill. Its substrate consisted of a 0.80-m thick mixture of sand and compost. The goal of this experiment was to evaluate the performance of the PMOB in reducing CH 4 emissions when submitted to an increasing methane load. The CH 4 load applied started with 0.3 g CH 4 m −2 h −1 . When the site had to be closed for the winter, the CH 4 input was 27 g CH 4 m −2 h −1 . Throughout the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 35 publications
2
27
0
2
Order By: Relevance
“…Another caveat is that the application of the method to field profiles may lead to an underestimation of the total oxidation efficiency if a relevant share of the oxidation occurs very near the surface (Cabral et al, 2009(Cabral et al, , 2010, while the top most samples of gas profiles are taken from below this upper crust. It is thus advisable to collect samples from as shallow depths as possible.…”
Section: Limitations Of the Proposed Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another caveat is that the application of the method to field profiles may lead to an underestimation of the total oxidation efficiency if a relevant share of the oxidation occurs very near the surface (Cabral et al, 2009(Cabral et al, , 2010, while the top most samples of gas profiles are taken from below this upper crust. It is thus advisable to collect samples from as shallow depths as possible.…”
Section: Limitations Of the Proposed Methodsmentioning
confidence: 99%
“…Setup of the first laboratory column study using mineral soils. (Cabral et al, 2009(Cabral et al, , 2010. The gravel-sand-compost mixture was compacted to 77% of the Proctor, again to simulate actual field conditions.…”
Section: Laboratory Column Studies and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biogas mass fluxes at the surface were calculated based on the results obtained using Equation 1 (according to Cabral et al, 2010a andPerera et al, 2002), corrected for the standard temperature and pressure (STP).…”
Section: Surface Methane Mass Flux Calculationsmentioning
confidence: 99%
“…Several studies have shown that a passive biosystem (where the biogas passes through the cover naturally, without pumping it) installed in the cover system (interim or fi-nal) can be a very effective complement to active systems in reducing fugitive emissions of methane and odorous substances (Abichou et al, 2006a;Cabral et al, 2010a;Capanema et al, 2013;Capanema et al, 2014;Geck et al, 2016;Lucernoni et al, 2016;Roncato and Cabral, 2012;Sadasivam and Reddy, 2014;Scheutz et al, 2009). Most of these studies documented the performance of passive biosystems in temperate climates, while (to the authors' knowledge) no field-scale studies have been performed to document the performance of passive biosystems in Brazil (a tropical country) and employing residual soils.…”
Section: Introductionmentioning
confidence: 99%